Affordable Portable Platform for Classic Photometry and Low-Cost Determination of Cholinesterase Activity - Keresteš, Ondřej; Pohanka, Miroslav (Biosensors, 2023)
Excessive use of pesticides could potentially harm the environment for a long time. The reason for this is that the banned pesticide is still likely to be used incorrectly. Carbofuran and other banned pesticides that remain in the environment may also have a negative effect on human beings. In order to provide a better chance for effective environmental screening, this thesis describes a prototype of a photometer tested with cholinesterase to potentially detect pesticides in the environment. The open-source portable photodetection platform uses a color-programmable red, green and blue light-emitting diode (RGB LED) as a light source and a TSL230R light frequency sensor. Acetylcholinesterase from Electrophorus electricus (AChE) with high similarity to human AChE was used for biorecognition. The Ellman method was selected as a standard method. Two analytical approaches were applied: (1) subtraction of the output values after a certain period of time and (2) comparison of the slope values of the linear trend. The optimal preincubation time for carbofuran with AChE was 7 min. The limits of detection for carbofuran were 6.3 nmol/L for the kinetic assay and 13.5 nmol/L for the endpoint assay. The paper demonstrates that the open alternative for commercial photometry is equivalent. The concept based on the OS3P/OS3P could be used as a large-scale screening system.
Keywords: Carbofuran; Acetylcholinesterase; affordable; acetylcholinesterasa; photometry; field-analysis; karbofuran; Humans; cholinesterase; pesticidy; open-source; point-of-care test; lidé; cholinesterasové inhibitory; Cholinesterases; pesticide; cholinesterasy; Cholinesterase Inhibitors; Pesticides